The relationship of serum vitamins A, D, E and LL-37 levels with allergic status, tonsillar virus detection and immune response - Varpu Elenius; Oscar Palomares; Matti Waris; Riitta Turunen; Tuomo Puhakka; Beate Rückert; Tytti Vuorinen; Tobias Allander; Tero Vahlberg; Mübeccel Akdis; Carlos A. Camargo Jr; Cezmi A. Akdis; et al. (PUBLIC LIBRARY SCIENCE, 2022)
BackgroundTonsils have an active role in immune defence and inducing and maintaining tolerance to allergens. Vitamins A, D, and E, and antimicrobial peptide LL-37 may have immunomodulatory effects. We studied how their serum levels were associated with allergy status, intratonsillar/nasopharyngeal virus detection and intratonsillar expression of T cell-and innate immune response-specific cytokines, transcription factors and type I/II/III interferons in patients undergoing tonsillectomy.Methods110 elective tonsillectomy patients participated. Serum levels of vitamins A, 25(OH)D, and E, LL-37 and allergen-specific IgE as well as nasopharyngeal/intratonsillar respiratory viruses were analyzed. The mRNA expression of IFN-alpha, IFN-beta, IFN-gamma, IL-10, IL-13, IL-17, IL-28, IL-29, IL-37, TGF-beta, FOXP3, GATA3, RORC2 and Tbet in tonsils were analyzed by quantitative RT-PCR.ResultsThe median age of the patients was 16 years (range 3-60), 28% of subjects had atopy, and 57% carried >= 1 respiratory virus in nasopharynx. Detection of viruses decreased by age. Higher vitamin A levels showed borderline significance with less viral detection (P = 0.056). Higher 25(OH) D was associated with less allergic rhinitis and atopy (P < 0.05) and higher vitamin E with less self-reported allergy (P < 0.05). In gene expression analyses, 25(OH)D was associated with higher IL-37, vitamin A with higher IFN-gamma and vitamin E with less IL-28 (P < 0.05). LL-37 was associated with less FOXP3, RORC2 and IL-17 in tonsils (P < 0.05).ConclusionsVitamin D and E levels were associated with less allergic disorders. Vitamin A was linked to antiviral and vitamin D with anti-inflammatory activity. LL-37 and was linked to T regulatory cell effects.